A Glycosylated Cationic Block Poly(β‐peptide) Reverses Intrinsic Antibiotic Resistance in All ESKAPE Gram‐Negative Bacteria. Issue 17 (19th February 2020) - Si, Zhangyong; Lim, Hui Wen; Tay, Moon Y. F.; Du, Yu; Ruan, Lin; Qiu, Haofeng; Zamudio‐Vazquez, Rubí; Reghu, Sheethal; Chen, Yahua; Tiong, Wen Shuo; Marimuthu, Kalisvar; De, Partha Pratim; et al.
Abstract: Carbapenem‐resistant Gram‐negative bacteria (GNB) are heading the list of pathogens for which antibiotics are the most critically needed. Many antibiotics are either unable to penetrate the outer‐membrane or are excluded by efflux mechanisms. Here, we report a cationic block β‐peptide (PAS8‐ b ‐PDM12) that reverses intrinsic antibiotic resistance in GNB by two distinct mechanisms of action. PAS8‐ b ‐PDM12 does not only compromise the integrity of the bacterial outer‐membrane, it also deactivates efflux pump systems by dissipating the transmembrane electrochemical potential. As a result, PAS8‐ b ‐PDM12 sensitizes carbapenem‐ and colistin‐resistant GNB to multiple antibiotics in vitro and in vivo. The β‐peptide allows the perfect alternation of cationic versus hydrophobic side chains, representing a significant improvement over previous antimicrobial α‐peptides sensitizing agents. Together, our results indicate that it is technically possible for a single adjuvant to reverse innate antibiotic resistance in all pathogenic GNB of the ESKAPE group, including those resistant to last resort antibiotics. Abstract : The glycosylated cationic β‐peptide PAS8‐ b ‐PDM12 sensitizes the drug‐resistant ESKAPE Gram‐negative bacteria to multiple antibiotics by facilitating penetration through the outer membrane, and by deactivating efflux pump systems, opening an avenue for novel combination therapies for life‐threatening bacterial infections.